2018
DOI: 10.5194/hess-22-1947-2018
|View full text |Cite
|
Sign up to set email alerts
|

Topography significantly influencing low flows in snow-dominated watersheds

Abstract: Abstract. Watershed topography plays an important role in determining the spatial heterogeneity of ecological, geomorphological, and hydrological processes. Few studies have quantified the role of topography in various flow variables. In this study, 28 watersheds with snow-dominated hydrological regimes were selected with daily flow records from 1989 to 1996. These watersheds are located in the Southern Interior of British Columbia, Canada, and range in size from 2.6 to 1780 km 2 . For each watershed, 22 topog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 39 publications
(56 reference statements)
3
30
2
Order By: Relevance
“…On the basis of an investigation of 70 catchments with different topographic complexity, Zimmer and Gannon () suggested that there is less groundwater storage and contributions to low flows are small in low relief catchments. Li et al () showed that catchments with rough topography had higher low flows, but conversely, Käser and Hunkeler () found that flat areas (i.e., valleys with alluvial aquifers) contributed significantly to streamflow in their selection of Alpine catchments. We found a weak negative correlation between specific discharge and the fraction of the catchment with slopes <20° (Figure ), suggesting that flatter areas contribute less to streamflow during low‐flow conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of an investigation of 70 catchments with different topographic complexity, Zimmer and Gannon () suggested that there is less groundwater storage and contributions to low flows are small in low relief catchments. Li et al () showed that catchments with rough topography had higher low flows, but conversely, Käser and Hunkeler () found that flat areas (i.e., valleys with alluvial aquifers) contributed significantly to streamflow in their selection of Alpine catchments. We found a weak negative correlation between specific discharge and the fraction of the catchment with slopes <20° (Figure ), suggesting that flatter areas contribute less to streamflow during low‐flow conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The properties of these groundwater stores, and thus their responses to extended dry periods, vary markedly from place to place, so that the magnitude of low flows can also be highly variable in space (e.g., Floriancic et al, 2018;Smakhtin, 2001;Sun, Kasahara, Otsuki, Saito, & Onda, 2017). Previous studies have shown that landscape characteristics, like topography (Kroll, Luz, Allen, & Vogel, 2004;Kuentz, Arheimer, Hundecha, & Wagener, 2017;Li et al, 2018;Sayama et al, 2011;Staudinger, Weiler, & Seibert, 2015), geology (Tague & Grant, 2004), land use (Ahn & Merwade, 2017;Smakhtin, 2001), or the extent of quaternary deposits and unconsolidated layers (Roy & Hayashi, 2009;Winkler et al, 2016) can affect the magnitude of low flows. For example, Karlsen et al (2016) showed that for subcatchments of the Krycklan basin in Sweden, specific discharge during the summer low-flow period increased with catchment area and with the fraction of area characterized by deeper sediment deposits, but summer low flows were smaller in catchments with denser forest cover.…”
Section: Introductionmentioning
confidence: 99%
“…Low flows are typically defined from the minimum flow that is not exceeded for a given duration on an annual basis (e.g., Foster, 1924;Smakhtin, 2001) or from hydrograph recession analysis (e.g., Brutsaert & Nieber, 1977;Kirchner, 2009;Tallaksen, 1995). Characteristics of low flows, such as their frequency, magnitude, and duration, can be related to basin characteristics like elevation, slope, and other topographic drivers (e.g., Li et al, 2018;Mutzner et al, 2013;Staudinger et al, 2017) or to climate characteristics such as seasonal precipitation or temperature patterns (e.g., Giuntoli, Renard, Vidal, & Bard, 2013; Jenicek, Seibert, Zappa, Staudinger, & Jonas, 2016). Water balance models have also been used for low-flow prediction (Fahey et al, 2010;Pushpalatha, Perrin, Le Moine, Mathevet, & Andreassian, 2011), and rainfall-runoff models have been specifically calibrated for low flows (Garcia et al, 2017;Singh & Frevert, 2002;Staudinger, Weiler, & Seibert, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The two Budyko‐based approaches produced very consistent results; that is, about 33–35% increase in streamflow was due to human activities whereas the remaining was due to climate variability. The higher contribution of climate change than human activities is reasonable considering that the vast area of the upper HRB is located in the mountainous regions with a very low population density, whereas climate change is significant and manifests in the form of rapid increases in air temperature and precipitation and substantial variations of the cryospheric processes (Cheng et al, ; Li, Wei, et al, ; Zhang, Zheng, Wang, & Yao, ). Moreover, the finding is in line with the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, these methods were used to separate impacts on streamflow. In this research, we also applied them to distinguish impacts on surface run‐off and baseflow, as did by Li et al (). The parameter values for each time‐trend method were estimated using the linear or nonlinear least square regression methods.…”
Section: Methodsmentioning
confidence: 99%